Community-Based Learning as a Student Portfolio in Culinary Courses with Conjoint Analysis - winanti winanti (Universitas Insan Pembangunan Indonesia, 2023)
This study aims to describe a practice approach to building a learning community based on portfolio assessment carried out in the culinary community. The method used in this study is a qualitative method using direct observation, interviews, and documentation. The results showed that the student's portfolio resulted from cooking practice, where the cooking practice started from choosing a recipe, choosing the right ingredients, doing the cooking process, validating, and getting feedback. The whole learning process is carried out properly and accompanied by teachers and chefs to produce a student portfolio consisting of 5 components, namely student identity, activities followed, rating results, competencies, and certification types of student competencies through the portfolio. The results of the practice can be seen in the student portfolios in the learning community system. It can be seen the experience of students in participating in cooking practices and the number of scores on the like button and the number of reviews on the view comments in each student's portfolio. The most important factor in a learning community in the culinary field is a portfolio of 15,252, followed by a login factor of 13,112 and a collaboration of 11,132, so the author conducts research focusing on student portfolios. This study only discusses the results of cooking practice as a student portfolio in the learning community and does not discuss what features are used in practice and portfolios